Influence of graphene nanoplatelets on tribological properties of short carbon fibre reinforced PA-66/TCE composites. (2021) - Deepa Urs, M.V.; Suresha, B.; Hemanth, G.; Kulkarni, Giriraj; Shiva Charan, M.R.
Abstract: Graphene nanoplatelets (GNPs) modified thermoplastic-polymer based composite structures can be used as lightweight, damping, high strength, and tribo-elements in food processing machinery where traditional single materials become unproductive. In the present research work, novel GNPs modified polyamide 66/thermoplastic copolyester elastomer (PA 66/TCE) composite reinforced with short carbon fibres were developed. The possible structural changes of the materials by Fourier transformed infrared (FTIR) technique and the wear performance of the fabricated composites were investigated in adhesive wear and abrasive wear modes. Adhesive wear test was carried out at 1000, 3000, and 5000 m sliding distances and 50 N applied load and at 2 ms −1 sliding velocity. In case of abrasive wear, tests have been conducted at 300, 450, and 600 m abrading distances and at an applied normal load of 20 N using 425 µm silica sand particles as abrasives. For the GNPs modified PA 66/TCE hybrid composites used in this investigation, the friction coefficient increases with an increase in sliding distance and the specific wear rate decreased with an increase in sliding distance. Furthermore, superior wear performance was observed in 3 wt% GNPs modified PA 66/TCE hybrid composite. However, under three-body abrasion, the specific wear rate decreases with increase in abrading distance and the superior abrasion resistance were found in 1 wt% GNPs modified PA 66/TCE hybrid composites. Finally, the microscopy indicated significant differences in the wear mechanisms in each adhesive and abrasive wear modes.